CULTURE AND THE PROBLEM OF ITS DEVELOPMENT - Sherzodbek Sharobiddinov (International Scientific and Current Research Conferences, 2023)
This article presents broad analytical concepts on the problem of succession in the formation of culture. Also, the article contains the scientific proposal and practical recommendations formulated by the author.